Long lasting non-cellular reactions in sterilized soils recapitulate most of the intermediates of the Krebs cycle - Clémentin Bouquet; Mounir Traïkia; Fanny Perrière; Benoit Kéraval; Gaël Alvarez; Loïc Louis; Martin Leremboure; Guillaume Voyard; Sébastien Fontaine; Anne-Catherine Lehours (Soil Biology and Biochemistry, 2026)

Impact of Neutrophil Extracellular Traps on Clinical Outcome after Subarachnoid Hemorrhage: A Translational Narrative Review - François Delvoye; Julie Lebeau; Cécile Oury; Céline D’Emal; Bernard Lambermont; Nathalie Layios; Didier Ledoux; Annie Dubuisson; Louis Deprez; Martin Moïse; Benoit Ho-Tin-Noé; Mikael Mazighi; et al. (Translational Stroke Research, 2026)
Aneurysmal subarachnoid hemorrhage (aSAH) remains associated with substantial morbidity and mortality despite best medical treatment. Increasing evidence implicates thrombo-inflammation (TI), driven by neutrophils and neutrophil extracellular traps (NETs), in the pathogenesis of delayed cerebral ischemia (DCI) and cognitive impairment. This narrative review summarizes experimental and clinical data linking neutrophil activation and NETs formation to DCI after aSAH and outlines emerging therapeutic strategies. This review was structured according to the SANRA (Scale for the Assessment of Narrative Review Articles) guidelines and followed general recommendations for narrative reviews. A comprehensive PubMed and clinicaltrials.gov search identified experimental and clinical studies published in English without time window, focusing on TI, neutrophil activation, or NETosis in the acute phase of aSAH. Past and ongoing clinical trials were classified by mechanism of action. Experimental models and human data show early and sustained neutrophil activation within cerebral and systemic compartments after aSAH. NETs promote microvascular thrombosis, blood-brain barrier disruption, microglial activation, and neuronal injury, ultimately contributing to DCI and long-term cognitive impairment. Outside the brain, NETs may also aggravate neurogenic pulmonary edema and cardiac dysfunction. In animal models, deoxyribonuclease I (DNase I) effectively degrades NETs, improving perfusion, limiting neuronal apoptosis, and enhancing recovery. Several ongoing trials target TI pathways, including the RESET trial, which evaluates the impact of IV DNase I on clinical outcome after aSAH. NETs produced after neutrophil activation may be central to DCI. Targeting NETs represents a promising translational path to improve cerebral and systemic outcomes after aSAH.

Limited variation in sorghum yield responses to diverse legume rotations under Sudano-Sahelian conditions - Louis-Marie Raboin; Eric Gozé; Oumarou Diallo; Guelika Kafando; Benoit Joseph Batieno; Julie Dusserre (Field Crops Research, 2026)

Techno-economic evaluation of retrofitting power-to-methanol: grid-connected energy arbitrage vs standalone renewable energy - Siphesihle Mbatha; Payam G. Panah; Xiaoti Cui; Paulo Debiagi; Benoit Louis; Nicholas M.Musyoka; Raymond C. Everson; Ksenia Parkhomenko; Henrietta W. Langmi (Fuel, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The ganglioside GD3 and its synthase (ST8SIA1) as novel senescence markers associated with osteoarthritis - Christina Fissoun; Georges Maroun; Raissa Silva; Margot Milano; Benoit Guibert; Louis Dagneaux; Rosanna Ferreira-Lopez; Thérèse Commes; Eric Gilson; Christian Jorgensen; Julien Cherfils-Vicini; Yves-Marie Pers; et al. (GeroScience, 2025)

Monolithic TiO2-CeO2 and Pt/TiO2-CeO2@VUKOPOR®A foams in oxidation of dichloromethane and methanol - Ivana Troppová; Lenka Matějová; Kateřina Karásková; Satu Pitkäaho; Vasiliki Papaefthimiou; Benoit Louis; Ondřej Kania; Riitta L. Keiski (Journal of Environmental Chemical Engineering, 2025)

A guiding framework for hyperconnected circular supply chain implementation - Ziqing Wu; Raphaël Oger; Matthieu Lauras; Louis Faugère; Benoit Montreuil (Journal of Cleaner Production, 2025)

Metabolomic monitoring of chicory during in vitro gastrointestinal digestion and correlation with bioactive properties - Céline L. Pouille; Camille Dugardin; Josette Behra; Melissa Tourret; Roland Molinié; Jean-Xavier Fontaine; David Mathiron; Cécile Palaric; David Gagneul; Rozenn Ravallec; Caroline Rambaud; Jean-Louis Hilbert; et al. (Food Chemistry, 2025)

Biodegradable twine for trawl fishing: Seawater ageing and net modelling - Louis Le Gué; Mael Arhant; Peter Davies; Benoit Vincent; Erwan Tanguy (Marine Pollution Bulletin, 2025)

The root of plant-plant interactions: Belowground special cocktails - Laura Mathieu; Elsa Ballini; Jean-Benoit Morel; Louis-Valentin Méteignier (Current Opinion in Plant Biology, 2024)

Evolution, control and success of combination therapy with Ampicilin-sulbactam/Ceftazidime-Avibactam during a Carbapenem-Resistant Acinetobacter baumannii outbreak in burn Intensive Care Unit - Emmanuel Dudoignon; Francois Caméléna; Matthieu Lafaurie; Benjamin Deniau; Maité Chaussard; Maxime Coutrot; Lucie Guillemet; Alexandru Cupaciu; Alexandre Pharaboz; Louis Boutin; Mourad Benyamina; Marc Chaouat; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Use of linear features by mammal predators and prey in managed boreal forests - Arnaud Benoit-Pépin; Mariano Javier Feldman; Louis Imbeau; Osvaldo Valeria (Forest Ecology and Management, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Partial-body cryostimulation does not impact peripheral microvascular responsiveness but reduces muscular metabolic O2 consumption (m V ˙ O2) at rest - Dimitri Theurot; Olivier Dupuy; Julien Louis; Wafa Douzi; Renée Morin; Coralie Arc-Chagnaud; Benoit Dugué (Cryobiology, 2023)

Mitigating plastic pollution at sea: Natural seawater degradation of a sustainable PBS/PBAT marine rope - Louis Le Gué; Peter Davies; Mael Arhant; Benoit Vincent; Erwan Tanguy (Marine Pollution Bulletin, 2023)

Analysis of the structure and function of the LYK cluster of Medicago truncatula A17 and R108 - Thi-Bich Luu; Noémie Carles; Louis Bouzou; Chrystel Gibelin-Viala; Céline Remblière; Virginie Gasciolli; Jean-Jacques Bono; Benoit Lefebvre; Nicolas Pauly; Julie Cullimore (Plant Science, 2023)

Mortality of marine mussels Mytilus edulis and M. galloprovincialis : systematic literature review of risk factors and recommendations for future research - Coralie Lupo; Stéphanie Bougeard; Véronique Le Bihan; Jean Louis Blin; Gwenhael Allain; Patrick Azéma; Fabienne Benoit; Christian Béchemin; Ismaël Bernard; Philippe Blachier; Léa Brieau; Morgane Danion; et al. (Reviews in Aquaculture, 2021)
The aim of this study was to summarise the literature reporting the risk factors for mortality in the mussel species Mytilus edulis and Mytilus galloprovincialis in order to identify potential science‐based solutions to prevent or mitigate mussel mortality outbreaks. We followed the PRISMA methodology: Preferred Reporting Items for Systematic Reviews and Meta‐Analyses. The studied corpus of 91 publications (114 studies) was highly heterogeneous with respect to the methodological approaches used to define or estimate mussel mortality and the related putative risk factors. Results showed that the mortality risk of both mussel species M. edulis and M. galloprovincialis varied across the seasons, increased with an elevated seawater temperature above a thermal threshold of 20 and 24°C, respectively, decreased by protecting mussels from predation, and was associated with the presence of pathogens in M. edulis . For M. galloprovincialis , using mussel spat from the same area where the farming is carried out and farming them together with another mussel species appears to reduce the mortality risk. However, for M. edulis , this could be achieved by using pure crosses and in particular mussel spat having a selected genotype. For wild bed conservation, sand accumulation and anthropogenic sedimentation should be minimised. Our analysis showed that current approaches to this research topic are limited and are unlikely to yield actionable evidence to identify mussel mortality prevention or mitigation strategies. Therefore, recommendations are offered to increase the ability of future eco‐epidemiological research to identify multiple exposures associated with mussel mortality, underpinned by standardised efforts and cooperative initiatives.

The use of whole-body cryotherapy: time- and dose-response investigation on circulating blood catecholamines and heart rate variability - Julien Louis; Dimitri Theurot; Jean-Robert Filliard; Marielle Volondat; Benoit Dugué; Olivier Dupuy (European Journal of Applied Physiology, 2020)
Purpose A predominance of parasympathetic drive is observed following cold exposure. Such modulation of the autonomic nervous system (ANS) is associated with faster post-exercise recovery. Within this context, whole-body cryotherapy (WBC) has been spreading in sport medicine, though the optimal temperature and frequency are unclear. The aim of this study was to examine the effects of different cryotherapy conditions on the sympathovagal balance. Methods Forty healthy males were randomly assigned into five different groups (− 110 °C, − 60 °C, − 10 °C, control temperature [≃ 24 °C]) and undertook 5 WBC sessions over 5 consecutive days. Cardiac autonomic activity was assessed through heart rate variability (HRV) using power density of high frequency (HF), root-mean square difference of successive R–R intervals (RMSSD) and sympathovagal balance (LF/HF). Systemic sympathetic activity was assessed via circulating blood catecholamines. Results Mean weekly RMSSD (pre: 48 ± 22 ms, post: 68 ± 29 ms) and HF (pre: 607 ± 692 ms 2 , post: 1271 ± 1180 ms 2 ) increased ( p < 0.05) from pre to post WBC, only in the − 110 °C condition. A rise in plasma norepinephrine was found after the first − 110 °C WBC session only (pre: 173 ± 98, post: 352 ± 231 ng L −1 , p < 0.01); whereas, it was not significant after the 5th session (pre: 161 ± 120, post: 293 ± 245 ng L −1 , p = 0.15). Conclusion These results suggest that one − 110 °C WBC exposure is required to stimulate the ANS. After five daily exposures, a lower autonomic response was recorded compared to day one, therefore suggesting the development of physiological habituation to WBC.

Intraspecific difference among herbivore lineages and their host‐plant specialization drive the strength of trophic cascades - Arnaud Sentis; Raphaël Bertram; Nathalie Dardenne; Jean‐Christophe Simon; Alexandra Magro; Benoit Pujol; Etienne Danchin; Jean‐Louis Hemptinne (Ecology Letters, 2020)
Trophic cascades – the indirect effect of predators on non‐adjacent lower trophic levels – are important drivers of the structure and dynamics of ecological communities. However, the influence of intraspecific trait variation on the strength of trophic cascade remains largely unexplored, which limits our understanding of the mechanisms underlying ecological networks. Here we experimentally investigated how intraspecific difference among herbivore lineages specialized on different host plants influences trophic cascade strength in a terrestrial tri‐trophic system. We found that the occurrence and strength of the trophic cascade are strongly influenced by herbivores’ lineage and host‐plant specialization but are not associated with density‐dependent effects mediated by the growth rate of herbivore populations. Our findings stress the importance of intraspecific heterogeneities and evolutionary specialization as drivers of trophic cascade strength and underline that intraspecific variation should not be overlooked to decipher the joint influence of evolutionary and ecological factors on the functioning of multi‐trophic interactions.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Development and implementation of eco-genomic tools for aquatic ecosystem biomonitoring: the SYNAQUA French-Swiss program - Estelle Lefrançois; Laure Apothéloz-Perret-Gentil; Philippe Blancher; Samuel Botreau; Cécile Chardon; Laura Crepin; Tristan Cordier; Arielle Cordonier; Isabelle Domaizon; Benoit J. D. Ferrari; Julie Guéguen; Jean-Christophe Hustache; et al. (Environmental Science and Pollution Research, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Evaluating the influence of ecology, sex and kinship on the social structure of resident coastal bottlenose dolphins - Marie Louis; Benoit Simon-Bouhet; Amélia Viricel; Tamara Lucas; François Gally; Yves Cherel; Christophe Guinet (Marine Biology, 2018)

Hyperspectral core logging for fire reconstruction studies - Antonin Van Exem; Maxime Debret; Yoann Copard; Boris Vannière; Pierre Sabatier; Stephane Marcotte; Benoit Laignel; Jean-Louis Reyss; Marc Desmet (Journal of Paleolimnology, 2018)

The Hevea brasiliensis XIP aquaporin subfamily: genomic, structural and functional characterizations with relevance to intensive latex harvesting - David Lopez; Maroua Ben Amira; Daniel Brown; Beatriz Muries; Nicole Brunel-Michac; Sylvain Bourgerie; Benoit Porcheron; Remi Lemoine; Hervé Chrestin; Ewan Mollison; Alessandra Di Cola; Lorenzo Frigerio; et al. (Plant Molecular Biology, 2016)

Lead exposure through consumption of big game meat in Quebec, Canada: risk assessment and perception - Richard Coovi Fachehoun; Benoit Lévesque; Pierre Dumas; Antoine St-Louis; Marjolaine Dubé; Pierre Ayotte (Food Additives & Contaminants: Part A, 2015)

Molecular Rescue of DYRK1A Overexpression in Cystathionine Beta Synthase-Deficient Mouse Brain by Enriched Environment Combined with Voluntary Exercise - Benoit Souchet; Alizée Latour; Yuchen Gu; Fabrice Daubigney; Jean-Louis Paul; Jean-Maurice Delabar; Nathalie Janel (Journal of Molecular Neuroscience, 2015)

Pre-winter distribution and habitat characteristics of polar cod (Boreogadus saida) in southeastern Beaufort Sea - Delphine Benoit; Yvan Simard; Louis Fortier (Polar Biology, 2014)

Habitat‐driven population structure of bottlenose dolphins, T ursiops truncatus , in the N orth‐ E ast A tlantic - Marie Louis; Amélia Viricel; Tamara Lucas; Hélène Peltier; Eric Alfonsi; Simon Berrow; Andrew Brownlow; Pablo Covelo; Willy Dabin; Rob Deaville; Renaud de Stephanis; François Gally; et al. (Molecular Ecology, 2014)
Despite no obvious barrier to gene flow, historical environmental processes and ecological specializations can lead to genetic differentiation in highly mobile animals. Ecotypes emerged in several large mammal species as a result of niche specializations and/or social organization. In the N orth‐ W est A tlantic, two distinct bottlenose dolphin ( T ursiops truncatus ) ecotypes (i.e. ‘coastal’ and ‘pelagic’) have been identified. Here, we investigated the genetic population structure of N orth‐ E ast A tlantic ( NEA ) bottlenose dolphins on a large scale through the analysis of 381 biopsy‐sampled or stranded animals using 25 microsatellites and a 682‐bp portion of the mitochondrial control region. We shed light on the likely origin of stranded animals using a carcass drift prediction model. We showed, for the first time, that coastal and pelagic bottlenose dolphins were highly differentiated in the NEA . Finer‐scale population structure was found within the two groups. We suggest that distinct founding events followed by parallel adaptation may have occurred independently from a large A tlantic pelagic population in the two sides of the basin. Divergence could be maintained by philopatry possibly as a result of foraging specializations and social organization. As coastal environments are under increasing anthropogenic pressures, small and isolated populations might be at risk and require appropriate conservation policies to preserve their habitats. While genetics can be a powerful first step to delineate ecotypes in protected and difficult to access taxa, ecotype distinction should be further documented through diet studies and the examination of cranial skull features associated with feeding.

The MISTIGRI thermal infrared project: scientific objectives and mission specifications - Jean-Pierre Lagouarde; Michel Bach; José A. Sobrino; Gilles Boulet; Xavier Briottet; Selma Cherchali; Benoit Coudert; Isabelle Dadou; Gérard Dedieu; Philippe Gamet; Olivier Hagolle; Frédéric Jacob; et al. (International Journal of Remote Sensing, 2013)

Biological invasions in soil: DNA barcoding as a monitoring tool in a multiple taxa survey targeting European earthworms and springtails in North America - David Porco; Thibaud Decaëns; Louis Deharveng; Samuel W. James; Dariusz Skarżyński; Christer Erséus; Kevin R. Butt; Benoit Richard; Paul D. N. Hebert (Biological Invasions, 2013)

Life strategy and diet of Calanus glacialis during the winter–spring transition in Amundsen Gulf, south-eastern Beaufort Sea - Anette Wold; Gérald Darnis; Janne E. Søreide; Eva Leu; Benoit Philippe; Louis Fortier; Michel Poulin; Gerhard Kattner; Martin Graeve; Stig Falk-Petersen (Polar Biology, 2011)

Optimized assay and storage conditions for enzyme activity profiling of ectomycorrhizae - Karin Pritsch; Pierre Emanuel Courty; Jean-Louis Churin; Benoit Cloutier-Hurteau; Muhammad Arif Ali; Coralie Damon; Myriam Duchemin; Simon Egli; Jana Ernst; Laurence Fraissinet-Tachet; Francisco Kuhar; Elvira Legname; et al. (Mycorrhiza, 2011)

From polar night to midnight sun: photoperiod, seal predation, and the diel vertical migrations of polar cod (Boreogadus saida) under landfast ice in the Arctic Ocean - Delphine Benoit; Yvan Simard; Jacques Gagné; Maxime Geoffroy; Louis Fortier (Polar Biology, 2010)

Severe Drug-induced Liver Injury Associated with Prolonged Use of Linezolid - Liesbet De Bus; Pieter Depuydt; Louis Libbrecht; Linos Vandekerckhove; Joke Nollet; Dominique Benoit; Dirk Vogelaers; Hans Van Vlierberghe (Journal of Medical Toxicology, 2010)

The determinants of prevalence of health complaints among young competitive swimmers - Benoit Lévesque; Jean-François Duchesne; Suzanne Gingras; Robert Lavoie; Denis Prud’Homme; Emmanuelle Bernard; Louis-Philippe Boulet; Pierre Ernst (International Archives of Occupational and Environmental Health, 2006)

Differentiation at a microgeographical scale within two species of ground beetle, Carabus auronitens and C. nemoralis (Coleoptera, Carabidae): a geometrical morphometric approach - Paul Alibert; Benoit Moureau; Jean‐Louis Dommergues; Bruno David (Zoologica Scripta, 2001)
New morphometric methods, the geometrical morphometrics, offer promising perspectives to appraise morphological variation among organisms and open up, to a large extent, the field of morphometrics for the study of systematics and evolution. Until now, however, few studies have explored the potential of these methods at a microgeographical scale. In the present work, we applied them to quantify morphological (size and shape) differentiation among populations of two forest species of ground beetles: Carabus auronitens and C. nemoralis . We found a significant shape variation among sites, as well as among sexes, for both species. Additionally, for C. auronitens , we found significant positive correlations in both sexes between morphological (shape) and geographical distances between populations. In contrast, significant size differences were found between sexes, but not between sites. We conclude that geometrical morphometric methods provide valuable tools for the study of morphological variation among populations and therefore offer, on the whole, interesting perspectives for the study of biodiversity patterns.

Association of the 5′ HS4 sequence of the chicken β‐globin locus control region with human EF1α gene promoter induces ubiquitous and high expression of human CD55 and CD59 cDNAs in transgenic rabbits - Frédérique Taboit‐Dameron; Benoit Malassagne; Céline Viglietta; Claudine Puissant; Mathieu Leroux‐Coyau; Christiane Chéreau; Joé Attal; Bernard Weill; Louis‐Marie Houdebine (Transgenic Research, 1999)